Predicting the Survival of Ischaemic Bowel in Preclinical Model Systems using Intraoperative Near-Infrared Fluorescence Angiography - Matsui, Aya (2011)
BACKGROUND: Predicting the long-term viability of ischaemic bowel during surgery is challenging. We hypothesized that intraoperative near-infrared (NIR) angiography (NIR-AG) of ischaemic bowel might provide metrics that were predictive of long-term outcome. MATERIALS AND METHODS: NIR-AG using indocyanine green (ICG) was performed on N = 24 pigs before and after inducing bowel ischaemia to determine the feasibility of NIR-AG to detect compromised perfusion. Contrast-to-background ratio (CBR) over time was measured in regions of interest throughout the bowel, and various metrics of the CBR-time curve were developed. N = 60 rat bowels, with or without strangulation, were imaged intraoperatively and on postoperative day (POD) 3. CBR metrics and clinical findings obtained intraoperatively were assessed quantitatively for their ability to predict animal survival, histological grade of ischaemic injury, and visible necrosis at POD 3. RESULTS: In the ischaemic bowels of pigs, various qualitative and quantitative CBR metrics appeared to correlate with bowel injury as a function of distance from normal bowel. In rats, intraoperative clinical assessment showed high specificity but low sensitivity for predicting outcome on POD 3. Qualitative patterns of the CBR-time curve, such as absence of an arterial inflow peak and presence of a NIR filling defect, resulted in better accuracies to predict animal survival, histological grade, and visible necrosis at POD 3 of 90%, 85% and 92%. CONCLUSION: Bowel survival at POD 3 can be predicted by intraoperative NIR-AG with higher accuracy compared to clinical evaluation alone. NIR-AG may someday prove useful clinically for avoiding unnecessary resection.